'Accountable Independence' of the European Central Bank: Seeing the Logics of Transparency. Issue 1 (August 2017) - Curtin, Deirdre
Abstract: The European Central Bank (ECB) emerged from the financial crisis not only as the institutional 'winner' but also as the most central—and powerful—supranational institution of our times. This article challenges the so‐called 'accountable independence' of the ECB across the range of tasks it carries out. Citizens 'see' the ECB today especially for its role in promoting austerity and its involvement as part of the troika and otherwise in the economic decision making of troubled Member States. Far from ECB monetary policy heralding a 'new democratic model', the ECB today suffers from a clear deficit in democracy. In between the grandiose concept of ECB 'independence' and the more performative ECB 'accountability' lies 'transparency'. Across the range of ECB practices there is a need to take the related concepts of 'transparency' and of (democratic) 'accountability' more seriously, both in conceptual terms and in their relationship to one another.